Agreement between an online dietary assessment tool (myfood24) and an interviewer-administered 24-h dietary recall in British adolescents aged 11–18 years. Issue 9 (15th March 2016) - Albar, Salwa A.; Alwan, Nisreen A.; Evans, Charlotte E. L.; Greenwood, Darren C.; Cade, Janet E.
Abstract: myfood24 Is an online 24-h dietary assessment tool developed for use among British adolescents and adults. Limited information is available regarding the validity of using new technology in assessing nutritional intake among adolescents. Thus, a relative validation of myfood24 against a face-to-face interviewer-administered 24-h multiple-pass recall (MPR) was conducted among seventy-five British adolescents aged 11–18 years. Participants were asked to complete myfood24 and an interviewer-administered MPR on the same day for 2 non-consecutive days at school. Total energy intake (EI) and nutrients recorded by the two methods were compared using intraclass correlation coefficients (ICC), Bland–Altman plots (using between and within-individual information) and weighted κ to assess the agreement. Energy, macronutrients and other reported nutrients from myfood24 demonstrated strong agreement with the interview MPR data, and ICC ranged from 0·46 for Na to 0·88 for EI. There was no significant bias between the two methods for EI, macronutrients and most reported nutrients. The mean difference between myfood24 and the interviewer-administered MPR for EI was −230 kJ (−55 kcal) (95 % CI −490, 30 kJ (−117, 7 kcal); P= 0·4) with limits of agreement ranging between 39 % (3336 kJ (−797 kcal)) lower and 34 % (2874 kJ (687 kcal)) higher than the interviewer-administered MPR. There was good agreement in terms of classifying adolescents into tertiles of EI ( κ w =0·64). The agreement between day 1 and day 2 was as good for myfood24 as for the interviewer-administered MPR, reflecting the reliability of myfood24. myfood24 Has the potential to collect dietary data of comparable quality with that of an interviewer-administered MPR.